Conditions of Successful Reintegration Ceremonies. Dealing with Juvenile Offenders - Braithwaite, John (The British journal of criminology, 1994)
Shifting criminal justice practices away from sligmalization and toward rcintegration is no small challenge. The innovation of community conferences in New Zealand and Australia has two structural features that are conducive to reinlegralive shaming: a selection of the people who respect and care most about the offender as conference participants conducing to rcintegration ; and b confrontation with victims conducing to shaming. Observation of some failures and successes of these conferences in reintegrating both offenders and victims is used to hypothesize 14 conditions of successful reinlegration ceremonies